Cardiac Hepatopathy: New Perspectives on Old Problems through a Prism of Endogenous Metabolic Regulations by Hepatokines - Berezin, A. A.; Obradovic, Z.; Berezina, T. A.; Boxhammer, E.; Lichtenauer, M.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2023)
Cardiac hepatopathy refers to acute or chronic liver damage caused by cardiac dysfunction in the absence of any other possible causative reasons of liver injury. There is a large number of evidence of the fact that cardiac hepatopathy is associated with poor clinical outcomes in patients with acute or actually decompensated heart failure (HF). However, the currently dominated pathophysiological background does not explain a role of metabolic regulative proteins secreted by hepatocytes in progression of HF, including adverse cardiac remodeling, kidney injury, skeletal muscle dysfunction, osteopenia, sarcopenia and cardiac cachexia. The aim of this narrative review was to accumulate knowledge of hepatokines (adropin; fetuin-A, selenoprotein P, fibroblast growth factor-21, and alpha-1-microglobulin) as adaptive regulators of metabolic homeostasis in patients with HF. It is suggested that hepatokines play a crucial, causative role in inter-organ interactions and mediate tissue protective effects counteracting oxidative stress, inflammation, mitochondrial dysfunction, apoptosis and necrosis. The discriminative potencies of hepatokines for HF and damage of target organs in patients with known HF is under on-going scientific discussion and requires more investigations in the future.
Keywords: heart failure; cardiac hepatopathy; inflammation; oxidative stress; hepatokines; adropin; fetuin-A; alpha-1-microglobulin; fibroblast growth factor-21; selenoprotein P